Remembering what did not happen: the role of hypnosis in memory recall and false memories formation - Leo, Donato Giuseppe; Bruno, Davide; Proietti, Riccardo (Frontiers in Psychology, 2025)
Memory recall is subject to errors that can lead to the formation of false memories. Several factors affect memory processes, such as attention deficits or emotional distress. Additionally, cardiovascular diseases may lead to cognitive decline and memory loss, also increasing the occurrence of false events recall. Hypnosis has proved to affect the autonomic nervous system, positively impacting the cardiovascular response. Hypnosis has also been suggested as a tool to enhance memory and autobiographical events recall in both healthy and unhealthy individuals; however, this approach has led to several controversies. Particularly, the employment of hypnosis in autobiographical recall (hypnotic regression) has been accused of favoring the creation of false memories, leading to therapeutic fallacy. In this paper, we review the current literature on the mechanisms behind the creation of false memories and the role played by hypnosis in memory enhancement and false memory recall. The evidence here collected suggests that cardiovascular diseases affect brain health contributing to cognitive decline and memory impairments, also increasing the occurrence of false memories. Hypnosis induces an increase in parasympathetic activity and a decrease in sympathetic activity, suggesting a potential role in preventing some cardiovascular diseases, such as hypertension, which in turn may improve brain health. Additionally, hypnosis has been shown to have some effectiveness in enhancing memory functions, although contradictory findings reported by several studies make it difficult to draw proper conclusions. Hypnotic regression and guided imagery should be used with caution as they may unintentionally lead to false memory recall. Nevertheless, further studies are required to better understand the effects of hypnosis on the brain and the heart and how it can be used to enhance memory, especially in people with cognitive decline.